The influence of knowledge worker characteristics on knowledge integration capacity among Malaysian knowledge workers - Noor Anida Zaria Mohd Noor (Tanjong Malim, 2019)
The influence of knowledge worker characteristics on knowledge integration capacity among Malaysian knowledge workers by Noor Anida Zaria Mohd Noor